2011
DOI: 10.1002/ejic.201001100
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Nanocrystalline TiO2 with Phosphonate‐ and Bis(phosphonate)‐Bearing Macrocyclic Complexes: Sorption and Stability Studies

Abstract: The first systematic study of chemical adsorption/desorption of phosphonic acid and geminal bis(phosphonic acid) on/ from the surface of anatase nanoparticles is reported. Stable TiO 2 colloidal nanodispersions were used in the study. The colloidal stability is preserved upon nanoparticle modification. A macrocyclic lanthanide(III) complex, attached through a phosphonic/bis(phosphonic) group to the TiO 2 surface allowed precise quantification of sorption parameters by means of inductively coupled plasma atomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 59 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…17 Greenwood et al found that silica sols could be efficiently grafted by slow addition of pre-hydrolyzed GPTMS. 32,33 Pautrot-d'Alençon et al modified CeO 2 sols stabilized by acetate groups using 2-carboxyethylphosphonic acid, ethylphosphonic acid, and phosphonoacetic acid in order to tune the acidic character of their surface. 4,18 Suspensions of positively charged silica particles stabilized at low pH (B4) are also commercially available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Greenwood et al found that silica sols could be efficiently grafted by slow addition of pre-hydrolyzed GPTMS. 32,33 Pautrot-d'Alençon et al modified CeO 2 sols stabilized by acetate groups using 2-carboxyethylphosphonic acid, ethylphosphonic acid, and phosphonoacetic acid in order to tune the acidic character of their surface. 4,18 Suspensions of positively charged silica particles stabilized at low pH (B4) are also commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…4,18 Suspensions of positively charged silica particles stabilized at low pH (B4) are also commercially available. 33 The goal of the present article is to explore the modification of aqueous sols of alumina-coated silica stabilized by electrostatic repulsions with different phosphonic acids, and to assess the influence of this modification on interactions and colloidal stability. The presence of this alumina coating opens the road to surface functionalization in aqueous medium using phosphonic acids (PAs), as recently shown for aggregated silica nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The modier can be acids, amines, alcohols, silanes, phosphonates, sulfonates and so on. 6,12,13,15,19,[23][24][25] A combination of more than two different approaches is also feasible such as TiO 2 -ZrO 2 -acrylic acid. 12 In this research, we used a one-step approach to make nanoparticles of aromatic phenyl acetic acid modied TiO 2 (PAA-TiO 2 ) and aliphatic hexanoic acid modied TiO 2 (HA-TiO 2 ) that are compatible with poly(ethoxylated (6) bisphenol A dimethacrylate).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, titania has been considered as a matrix material, which is attractive due to its thermal and mechanical stability. [31][32][33] In addition, the photocatalytic activity and energy conversion ability of titania make it promising for various potential applications. 19,33,34 For example, Li and coworkers have synthesized lanthanide hybrids through chemical modication of titanium alkoxide where lanthanide complexes can be anchored within the framework of inorganic titania materials.…”
Section: Introductionmentioning
confidence: 99%